AMINO-SUBSTITUTED PORPHYRINS AT THE BORDER OF HYBRID MATERIALS GENERATION AND PLATINUM NANOPARTICLES DETECTION - ANGHEL, Diana; BIRDEANU, Mihaela; LASCU, Anca; EPURAN, Camelia; FAGADAR-COSMA, Eugenia (Studia Universitatis Babeș-Bolyai Chemia, 2020)
Two amino substituted porphyrins, namely: 5,10,15,20-tetrakis(4-aminophenyl)porphyrin (TAPP) and 5,10,15,20-tetrapyridyl-21H,23H-porphine (TPyP) have been used for complexation reaction of platinum nanoparticles (PtNPs) with the main purpose to recover or detect them from diluted leaching solutions, after transformation in colloidal solutions. The complexation reactions were monitored by UV-vis spectroscopy and revealed that both porphyrins have the capacity to complex PtNPs in different detection domains ranging from 2.776 to 40.457 x 10-6 M in the case of TAPP, and in a larger range of 8.07 x 10-6 – 7.03 x 10-5 M in the case of TPyP. Excellent correlation coefficients of 99.35 % and 99.57 % respectively have been obtained in each case. During complexation a nanomaterial based on TAPP and a micromaterial composed from TPyP both having as second partner PtNPs were obtained and thoroughly characterized by atomic force microscopy (AFM). The aggregation phenomena that occurred for each amino-porphyrin in DMF, in their acidified solutions and in their hybrid materials, revealed that the TAPP-PtNPs hybrid is a nanomaterial, based on triangular prisms aggregates of acidulated TAPP, and the TPyP-PtNPs hybrid is a micromaterial that is based on pyramidal shaped aggregated from the acidulated solution of TPyP.